BRAND IMAGE, PRICE, AND PROMOTION: HOW DO THEY AFFECT SAMSUNG SMARTPHONE PURCHASE DECISIONS - Prasetya, Hendra; Azizah, Nurul (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
This study seeks to analyze how brand image, price, and promotion impact the buying choices of SAMSUNG brand smartphones among students at the Faculty of Economics and Business, Wijaya Kusuma University Surabaya. The target group for this research includes students enrolled in the Faculty of Economics and Business at Wijaya Kusuma University in Surabaya. The sample characteristics include FEB UWKS students who have purchased and used SAMSUNG brand smartphones. The number of respondents in the sample was 96. The findings from the analysis of multiple linear regression and hypothesis testing using t-tests reveal that factors such as brand image, price, and promotion have a strong and favorable impact on the purchasing choices of SAMSUNG brand smartphones among students studying at the Faculty of Economics and Business in Wijaya Kusuma University, Surabaya. To improve consumer purchasing decisions, companies are expected to: (1) Enhance brand image by building a reputable company, increasing consumer satisfaction, and improving product quality; (2) Set more affordable prices that align with quality and benefits and maintain competitiveness; and (3) Conduct promotions that: (a) Utilize various promotional media and (b) Convey clear, interesting, and easy-to-understand messages.